Relação entre risco cardiovascular e qualidade de vida de pacientes hemodialisados - Oliveira, Lorrana Gabriella de (2018)
INTRODUCTION: patients with chronic kidney disease have variable increase in the risk of developing cardiovascular events, since both have common risk factors. The numerous changes and adaptations undergone by these patients impose a considerable psychosocial overload on patients and their families, which can be aggravated by the existence of comorbidities and compromise their quality of life. OBJECTIVE: to analyze the relationship between cardiovascular risk and health related quality of life in hemodialysis patients in Goiânia-GO. METHODS: an analytical cross-sectional study performed with 339 patients at eight hemodialysis clinics in the city of Goiânia, state of Goiás, from January to September 2017. For data collection, a questionnaire was used with sociodemographic, clinical and laboratory variables; the Kidney Disease Outcomes Quality Initiative-Short Form (KDQOL-SF), to obtain measures of quality of life and the Framingham Score for cardiovascular risk measurement. To analyze the data, normality tests were applied for parametric and non-parametric variables. RESULTS: population comprised of 60.8% of men, with mean age of 52 years and personal income of a minimum wage. Most of the patients were non-smokers, had Systemic Arterial Hypertension and Diabetes Mellitus as the main comorbidities. The most impaired quality of life dimensions were "professional role" followed by "renal disease overload". The dimensions "cognitive function" and "quality of social interaction" presented better performance. The majority of the studied population (42.3%) had a moderate cardiovascular risk. CONCLUSION: patients with high cardiovascular risk in lower consumption in seven domains of quality of life, in relation to those with medium and low cardiovascular risk, being “physical functioning”, "physical function," "general health," "emotional function," and "kidney disease overload," demonstrating that there was a negative correlation between quality of life and cardiovascular risk.